The Impact of Internal and External Variables on Non-performing Financing (NPF) of Islamic Banks in Indonesia - Chandra Setiawan; Purwanto Purwanto; Pandu Adi Cakranegara (Universitas Muhammadiyah Yogyakarta, 2024)
Islamic banking financing continues to experience better growth and provides great contributions in Indonesia. This industry must innovate products and improve its performance. This research paper aims to improve the Non-Performing Financing (NPF) and efficiency model of Islamic commercial banks in Indonesia while enhancing the quality of governance in the banking industry. In this study, researchers used Data Envelopment Analysis (DEA) to process overall technical efficiency (OTE) and panel regression to establish the causal relationship between independent and dependent variables, both partially and simultaneously. Researchers also analyzed the correlational association between NPF and the efficiency of Islamic banks in Indonesia. The data used in the study were obtained from Islamic commercial banks that were consistently published by Bank Indonesia and the Bank's database. Various micro or internal banking variables were used, and external variables, such as macro variables, were found to influence NPF. The study identified internal variables like CAR and FDR and external variables like GDP and inflation of Islamic banking in Indonesia that significantly impact NPF. Furthermore, the study results suggest that the FDR variable is among the significant variables with the highest significance value. It was also found that the